Kinematic analysis of Balantak Fault using fault-slip data in Balantak area, Banggai Regency, Central Sulawesi - Endinanda, Ferdi (Berita Sedimentologi, 2022)
Balantak is one of the sub-districts in Banggai Regency, Central Sulawesi Province. The research area is along the Balantak Strike-Slip Fault. This study presents geological mapping with focus on the deformation style that occurred within the area. The study provides an analogue of strike-slip structural trap types in convergent setting to support oil and gas field development. This research method was conducted using field observation and kinematic analysis of fault-slip data. Lithology in the study area that is part of the Banggai-Sula microplate has the characteristics of sedimentary rocks that are grainstone intercalating calcareous sandstone and rudstone consisting of limestone fragments. While part of the Sulawesi East Arm has crystalline rocks in the form of ultramafic-mafic rocks such as Peridotite, Serpentinite, Gabbro and Basalt. Structural analysis along the strike-slip fault indicates the collision of Banggai-Sula with Sulawesi East Arm on the side part of the micro-plate generates thrust fold belt along with well-developed uniform tearing faults present. The orientation and shape of the strain ellipsoid is pure shear transpression with the Balantak Fault as its plane of movement. The characteristic of the structure pattern complying with the model shows that the type of structures is en echelon thrusts and folds while the tearing faults are Riedel synthetics of the Balantak dextral Strike-Slip Fault that developed offset on the fold structures.